Genetic damage in Goodea atripinnis (Goodeidae) and persistent organic-compounds in both Chapala and Sayula Lakes, in Mexico - Reynoso Silva, Mónica; Arévalo Hernández, Armando; Feria Velasco, Alfredo; Álvarez Moya, Carlos (HIDROBIOLÓGICA, 2017)
POPs are a group of chemicals with genotoxic capacity, found as contaminants in many water bodies. Given the high chemical pollution of Chapala Lake (including POPs), consumption of this water poses a genotoxic risk for people in the Guadalajara metropolitan area. Concentrations of POPs were quantified in water from Chapala Lake, Sayula Lake and in the liver of Goodea atripinnis on two seasons of the year: the dry and rainy seasons of 2006. Chromatographic analysis of the water showed very low concentrations of POPs and variations from one season to another. The increase of methoxychlor, 2,4 D and DDT is notable, indicating that they are dragged into the water bodies during the rainy season. POPs were detected in the liver of fish from both lakes; however, 2,4 D in the liver of fish from Chapala (0.02 ppm) is 10 times as concentrated as in Sayula (0.002 ppm). The evaluation of genetic damage by alkaline comet assay in hepatocytes during the dry season showed significant genetic damage (p < 0.01) in fish from the two reservoirs, probably due to 2,4 D. In the rainy season there was a significant difference (p < 0.01) in the case of Sayula but not for Chapala. Genetic damage in Sayula can be attributed to other substances with a mutagenic capacity different to that of POPs.